1.由2a^2-3a+4=6得2a^2-3a=2
(1)-4a^2+6a-3=-2(2a^2-3a)-2=-4-2=-6
(2)8a^2-12a+5=4(2a^2-3a)+5=8+5=13
2.(4x+xy+2y)÷ (2x-4xy+y)=[2(2x+y)+xy]÷(10xy-4xy)
=21xy÷6xy=7/2
3.(a-b)÷(a+b)=4,则(a+b)÷(a-b)=1/4
[(2a-2b)÷(a+b)]-[(4a+4b)÷(3a-3b)]
=[2(a-b)÷(a+b)]-[4(a+b)]÷3(a-b)]
=8-1/3=23/3
4.3a-5b+19=0 a+8b-1=0
3a+24b-3=0
29b-22=0 b=22/29
a=1-8b=-147/29
-12a-9b=-3(4a+3b)=-3(4-32b+3b)=-3(4-29b)=-3(4-22)=-54
4a-26b=4-32b-26b=4-58b=4-44=-40
5.a^2-ab=1 4ab-3b^2=-2
(a^2)-9ab+6b^2-5
=a^2-ab-8ab+6b^2-5
=(a^2-ab)-2(4ab-3b^2)-5
=1+4-5
=0